2020
DOI: 10.1038/s41431-020-00768-8
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution population-specific recombination rates and their effect on phasing and genotype imputation

Abstract: Previous research has shown that using population-specific reference panels has a significant effect on downstream population genomic analyses like haplotype phasing, genotype imputation, and association, especially in the context of population isolates. Here, we developed a high-resolution recombination rate mapping at 10 and 50 kb scale using high-coverage (20–30×) whole-genome sequenced data of 55 family trios from Finland and compared it to recombination rates of non-Finnish Europeans (NFE). We tested the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 52 publications
1
17
0
Order By: Relevance
“…In this case, common ancestors within the past 20 generations (post-admixture in Cabo Verde) would give an expected IBD segment length of approximately 2.5 Mb or longer, so we applied 2.5 Mb as the shorter/long ROH boundary. This approximation uses the commonly applied baseline recombination rate of 1 cM/Mb, though we note that recombination varies among populations and along genomes (Hassan et al 2021). Under these two classification schemes, we examined the distributions of total ROH per genome (sum of ROH segments of a specific length) within Cabo Verde, partitioning the distributions into length classes that are enriched for pre- and post-colonization processes.…”
Section: Resultsmentioning
confidence: 99%
“…In this case, common ancestors within the past 20 generations (post-admixture in Cabo Verde) would give an expected IBD segment length of approximately 2.5 Mb or longer, so we applied 2.5 Mb as the shorter/long ROH boundary. This approximation uses the commonly applied baseline recombination rate of 1 cM/Mb, though we note that recombination varies among populations and along genomes (Hassan et al 2021). Under these two classification schemes, we examined the distributions of total ROH per genome (sum of ROH segments of a specific length) within Cabo Verde, partitioning the distributions into length classes that are enriched for pre- and post-colonization processes.…”
Section: Resultsmentioning
confidence: 99%
“…Finland is a well-established genetic isolate and a unique gene pool distinguishes Finns from other Europeans 7 . The distinct Finnish haplotype structure is characterized by large blocks of co-inherited DNA in linkage disequilibrium and an enrichment for alleles that are rare in other populations, but can still be confidently imputed from genotyping data even in the rare and ultra-rare allele frequency spectrum [8][9][10] . Through combining imputed genotypes with detailed phenotypes ascertained through national registries, FG holds the promise to provide particular insights into the so far little examined allele frequency spectrum between 0.1 and 2%, where both sequencing studies and GWAS have so far remained largely underpowered in relation to identifying associations with disease.…”
mentioning
confidence: 99%
“…3 and 4). However, it should be noted that recent studies found that population-specific recombination maps have little effect on phasing (Hassan et al 2020), imputation (Hassan et al 2020) and local ancestry inference (van Eeden, Uren, van der Spuy, et al 2021). Therefore, the combined Phase II HapMap recombination map's proxy status with regards to the Nama is dependent on the analysis that the map is used for.…”
Section: Discussionmentioning
confidence: 98%